2010
DOI: 10.3233/ves-2010-0362
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-pupillary responses in deaf subjects

Abstract: Pupillary dilation in response to sound stimuli is well established and is generally considered to represent a startle reflex to sound. We believe that the auditory-pupillary response represents not only a simple startle reflex to sound stimuli but also represents a reaction to stimulation of other sense organs, such as otolith organs. Eight young healthy volunteers without a history of hearing and equilibrium problems and 12 subjects with bilateral deafness participated in this study. Computer pupillography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, age differences between the groups may have confounded this effect ( Winn, 2016 ). Finally, Kitajima et al. (2010) assessed the pupil response to loud clicks in deaf participants and did not observe a difference in their response when compared with that of listeners with normal hearing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, age differences between the groups may have confounded this effect ( Winn, 2016 ). Finally, Kitajima et al. (2010) assessed the pupil response to loud clicks in deaf participants and did not observe a difference in their response when compared with that of listeners with normal hearing.…”
Section: Resultsmentioning
confidence: 99%
“…However, age differences between the groups may have confounded this effect (Winn, 2016). Finally, Kitajima et al (2010) assessed the pupil response to loud clicks in deaf participants and did not observe a difference in their response when compared with that of listeners with normal hearing. In summary, the relatively few studies directly assessing the effect of hearing status on the pupil dilation response to auditory stimuli have shown mixed results.…”
Section: Listener Factors Influencing the Pupil Dilation Response To ...mentioning
confidence: 99%
“…At least in part, the effects of vestibular afferents on cognitive functions could be mediated by the central noradrenergic system arising from the LC, whose neurons are affected by the labyrinthine input (Manzoni et al, 1989 ; Kaufman et al, 1992 ), as confirmed by the observation that vestibular stimulation induces changes in pupil size (Kitajima et al, 2010 , 2013 ), which is a reliable indicator of LC activity (Rajkowski et al, 1993 , 1994 ; Murphy et al, 2014 ). It should be reminded that the vestibular influences on the LC have been proposed as the cause of the development of hemispheric specialization, since, during foetal development, the asymmetric position of the head is likely to favor activation of the left labyrinth during maternal locomotion, leading to an asymmetric development of several central structures (Previc, 1991 ).…”
Section: Trigeminal Visceral and Vestibular Influences On Brain Funcmentioning
confidence: 93%
“…Because of these it could not be ascertained if the Cr enrichment occurred in the inner part of oxide scale or at the alloy surface. However, from TEM-EDS analysis [18], Cr enrichment was not found in the lower part of the Al 2 O 3 scale. Therefore Cr enrichment is thought to occur within the alloy surface.…”
Section: Resultsmentioning
confidence: 86%